Discrimination of Geographical Origin of Unroasted Kernels Argan Oil (Argania spinosa (L.) Skeels) Using Tocopherols and Chemometrics. (11th October 2021) - Elgadi, Sara; Ouhammou, Ahmed; Zine, Hamza; Maata, Nadia; Aitlhaj, Abderrahmane; El Allali, Hassan; El Antari, Abderraouf
Abstract : Valorisation of Argan oil requires the precise identification of different provenances markers. The concentration of tocopherol is regarded as one of the essential parameters that certifies the quality and purity of Argan oil. In this study, 39 Argan samples from six different geographical origins (Safi, Essaouira, Agadir, Taroudant, Tiznit, and Sidi Ifni) from the central west of Morocco were collected and extracted using cold pressing. The total tocopherol amount was found to range from 783.23 to 1, 271.68 mg/kg. Generally, γ -tocopherol has the highest concentration in Argan oil. It should also be noted that the geographical origin was found to have a strong effect on the amounts of all tocopherol homologues studied. Principal component analysis of tocopherol concentrations highlighted a significant difference between the different provenances. The content of tocopherol has also been found to be strongly influenced by the distance from the coast and altitude, whereas no significant effect was found regarding other ecological parameters. The prediction ability of the LDA models was 87.2%. The highest correct classification was revealed in coastal provenances (100%), and the lowest values were from the continental ones (71.4%). These results provide the basis for determining the geographical origins of Argan oil production with well-defined characteristics to increase the product's value and the income of local populations. In addition, this study provides a very promising basis for developing Argan varieties with a high content of tocopherol homologues, as well as contributing to the traceability and protection of Argan oil's geographical indication.